2019
DOI: 10.1089/vbz.2019.2450
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence ofAnaplasma phagocytophiluminIxodes ricinusandDermacentor reticulatusand Coinfection withBorrelia burgdorferiand Tick-Borne Encephalitis Virus in Western Ukraine

Abstract: Introduction: Tick-borne encephalitis virus (TBEV) and Borrelia burgdorferi, the causative agent of Lyme disease (LD), are widespread in Western Ukraine. However, relatively little is known about Anaplasma phagocytophilum in this region. This study examined patterns of infection with A. phagocytophilum in two tick vectors compared with the better studied TBEV and B. burgdorferi.Materials: Ticks were collected in three different ecosystems of the Western Ukraine during 2009–2014. Samples were examined for patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…garinii were detected. The presence of Lyme disease pathogens in D. reticulatus ticks has been previously reported in European countries [ 18 , 44 ]; thus, it is important to decipher their vector competence for these agents in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…garinii were detected. The presence of Lyme disease pathogens in D. reticulatus ticks has been previously reported in European countries [ 18 , 44 ]; thus, it is important to decipher their vector competence for these agents in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…ricinus ticks was 29.3% [48]. In contrast, a much lower rate (4.4%) was recently noted for I. ricinus ticks collected from the Ternopil region (Western Ukraine) [54].…”
Section: Resultsmentioning
confidence: 74%
“…Specifically, thus far, only a few studies have showed the prevalence rates of selected tick-borne pathogens in ixodid ticks from Ukraine [48][49][50][51][52][53][54]. Moreover, Ca.…”
mentioning
confidence: 99%
“…In Europe and North America, Ixodes scapularis and Ixodes ricinus are responsible for the transmission of the agent to animals and humans, and together with Borrelia burgdorferi they are considered important zoonosis and a public health problem (ASMAN et al, 2017;BEN;LOZYNSKYI, 2019;ELIAS et al, 2021;HAUCK et al, 2019;ROSEF;PAULAUSKAS;RADZIJEVSKAJA, 2009;SKARPHÉDINSSON et al, 2007;STAŃCZAK et al, 2004).…”
Section: Resultsmentioning
confidence: 99%